Ability of bacterial biphenyl dioxygenases from Burkholderia sp. LB400 and Comamonas testosteroni B-356 to catalyse oxygenation of ortho-hydroxychlorobiphenyls formed from PCBs by plants - Francova, K; Macková, M; Macek, T; Sylvestre, M (Environmental pollution (Barking, Essex, 2004)
Capacity of enzymes of the biphenyl/chlorobiphenyl pathway, especially biphenyl dioxygenase (BPDO) of two polychlorinated biphenyls (PCB) degrading bacteria, Burkholderia sp. LB400 and Comamonas testosteroni B-356, to metabolize ortho-substituted hydroxybiphenyls was tested.,These compounds found among plant products of PCB metabolism, are carrying chlorine atoms on the hydroxyl-substituted ring. The abilities of His-tagged purified LB400 and B-356 BPDOs to catalyze the oxygenation of 2-hydroxy-3-chlorobiphenyl, 2-hydroxy-5-chlorobiphenyl and 2-hydroxy-3,5-dichlorobiphenyl were compared. Both enzyme preparations catalyzed the hydroxylation of the three chloro-hydroxybiphenyls on the non-substituted ring. Neither LB400 BPDO nor B-356 BPDO oxygenated the substituted ring of the ortho-hydroxylated biphenyl. The fact that metabolites generated by both enzymes were identical for all three hydroxychlorobiphenyls tested; exclude any other mode of attack of these compounds by LB400 BPDOs than the ortho-meta oxygenation.
Keywords: polychlorované bifenyly; Oxygenases; katalýza; Oxidation-Reduction; Soil Pollutants; oxidace-redukce; Catalysis; gramnegativní bakterie; Comamonas testosteroni; Biodegradation, Environmental; Burkholderia; biodegradace; rostliny; Gram-Negative Bacteria; Plants; Polychlorinated Biphenyls; oxygenasy; látky znečišťující půdu